FORMATION OF MICROBIAL COMPLEX OF TYPICAL CHERNOZEM IN AGROCENOSIS OF WINTER WHEAT AT DIFFERENT AGRARIAN SYSTEMS - Патика, М. В.; Колодяжний, О. Ю. (Scientific Progress & Innovations, 2014)
Analysis of the formation of microbial complex of typical chernozem in agrocenosis of winter wheat has been analyzed. The level of differentiation of number of the basic physiological and taxonomic groups of microbes has been identified. Features of structure formation, the qualitative composition and diversity of bacterial complex at different agrarian systems and tillage of soil have been shown. It has been established that the systematic application of organic fertilizers allows to be optimized microbiological processes and contributes to increase of species diversity with a uniform distribution of the dominant forms of microorganisms.